1980
DOI: 10.1159/000128124
|View full text |Cite
|
Sign up to set email alerts
|

Trauma and Acetylsalicylic Acid-Induced Changes in Hemostasis during Liver Resection in the Rat

Abstract: The effect of acetylsalicylic acid and bilateral femoral crush fractures on hemostasis after liver resection was studied in the rat. Serum salicylate levels were dose-dependent and similar in traumatized and non-traumatized animals. Bleeding time was significantly shortened and blood loss significantly decreased after bilateral femoral crush fractures. Both these values were significantly increased in salicylate pretreated animals compared to controls. Combination of bilateral femoral crush fractures and admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

1984
1984
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Blood loss in the liver injury model with no treatment was 357.57 ± 267.31 µL and lasted the entire experimental period. These findings are similar to those in the literature when 2.5% to 4% of the liver was resected and bleeding lasted between 5–9 minutes with 1.0 to 3.4 mL of blood lost (Alwmark et al, 1986; Bengmark et al, 1980; Bengmark et al, 1981; Holcomb et al, 2000; Kullendorff et al, 1984; Lindfeldt et al, 1987; Tanaka et al, 1985; Zoucas et al, 1982; Zoucas et al, 1984a; Zoucas et al, 1984b;). Additionally, Holcomb et al (2000) demonstrated a reduction in blood loss by 52% using fibrin glue in a model of median hepatic lobe injury in rats.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Blood loss in the liver injury model with no treatment was 357.57 ± 267.31 µL and lasted the entire experimental period. These findings are similar to those in the literature when 2.5% to 4% of the liver was resected and bleeding lasted between 5–9 minutes with 1.0 to 3.4 mL of blood lost (Alwmark et al, 1986; Bengmark et al, 1980; Bengmark et al, 1981; Holcomb et al, 2000; Kullendorff et al, 1984; Lindfeldt et al, 1987; Tanaka et al, 1985; Zoucas et al, 1982; Zoucas et al, 1984a; Zoucas et al, 1984b;). Additionally, Holcomb et al (2000) demonstrated a reduction in blood loss by 52% using fibrin glue in a model of median hepatic lobe injury in rats.…”
Section: Discussionsupporting
confidence: 90%
“…Evaluations of existing techniques for determining blood loss were imprecise and highly variable. Historically, blood loss determinations in models of liver, spleen or kidney wound were performed using a preweighed aluminum cup (Bengmark et al, 1980; Kullendorff et al, 1984; Kullendorff and Zoucas, 1985; Lindblom et al, 1990; Lindfeldt et al, 1987; Vagianos et al, 1987; Zoucas et al, 1984a; Zoucas et al, 1984b;) or a stack of gauze pads (Holcomb et al, 2000; Tuthill et al, 2001) and determining final blood loss by weight. A more extensive search of the literature provided a protocol for hematin determination (Masci et al, 1988) and coupled with the use of Whatman filter paper “chads” this provided the desired accuracy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation